2017
DOI: 10.5001/omj.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Incidence and Risk Factor Patterns among Omanis with Type 2 Diabetes: A Retrospective Cohort Study

Abstract: This study revealed high incidence of CVD and high prevalence of its traditional risk factors among Omanis with T2DM. In addition, compared to global studies, important differences in the prevalence of some risk factors and their patterns in the univariate association with the cardiovascular outcome have been observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Globally, the incidence rates of CVD vary among different high-risk populations. The findings from a recent 5-year study conducted in a neighboring Arab country showed that the incidence rate of CVD among patients with diabetes was 17.6 per 1000 person-years, which is higher than the incidence rate determined in this study [6]. A Chinese study’s findings showed a CVD incidence rate of 17.2 per 1000 person-years among high-risk patients over 5 years [21].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Globally, the incidence rates of CVD vary among different high-risk populations. The findings from a recent 5-year study conducted in a neighboring Arab country showed that the incidence rate of CVD among patients with diabetes was 17.6 per 1000 person-years, which is higher than the incidence rate determined in this study [6]. A Chinese study’s findings showed a CVD incidence rate of 17.2 per 1000 person-years among high-risk patients over 5 years [21].…”
Section: Discussioncontrasting
confidence: 54%
“…The study’s sample size was calculated using a formula for a study designed to estimate incidence in a population [13]. A sample size of 923 was determined based on an anticipated 10% incidence of CVD [6] and utilizing 80% power at a 2-sided level of significance of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cardiovascular events may worsen T2DM symptoms and result in a higher risk of T2DM-related complications [ 28 ]. We adjusted for country income level, sex, and age; however, it may have been beneficial to further adjust for other risk factors such as high blood pressure [ 30 , 31 ]. Since this study is based on global aggregate data, we were unable to control for these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed higher incidence of CVD among diabetic patients as compared with studies conducted in the world. Studies in China (29) and Oman (30) showed that 17.2 and 17.6 per 1000 PY of CVD among DM within median follow up periods of 5.3 and 5.6 years, respectively. This difference was probable because of the higher proportion of DM patients in our study had hypertension which contribute to the risk for developing CVD, compared to general population (6).…”
Section: Predictors Of Cvd Among Diabetic Patientsmentioning
confidence: 99%